"Is it time to throw out the weighing scales?" Implicit weight bias among healthcare professionals working in bariatric surgery services and their attitude towards non-weight focused approaches. (January 2023) - Abbott, S.; Shuttlewood, E.; Flint, S.W.; Chesworth, P.; Parretti, H.M.
Summary: Background: People living with overweight or obesity (PLwO) can be stigmatised by healthcare professionals (HCPs). Reducing focus on weight is a proposed strategy to provide less threatening healthcare experiences. Given the lack of research on weight bias within obesity services, this study aimed to explore implicit bias among obesity specialist HCPs and explore views on non-weight focused approaches. Methods: Obesity specialist HCPs were invited to a webinar, "An exploration of non-weight focused approaches within bariatric services", held in October 2021. Implicit weight bias was examined using the BiasProof mobile device test, based on the Implicit Association Test. Poll data was analysed descriptively, and qualitative data was analysed using framework analysis. Findings: 82 of the 113 HCPs who attended the webinar consented to contribute data to the study. Over half (51%) had an implicit weight bias against PLwO. Most (90%) agreed/strongly agreed that obesity services are too weight focused and that patients should not be weighed at every appointment (86%). Perceived benefits of taking a non-weight focused approach included patient-led care, reducing stigma and supporting patient wellbeing, while perceived barriers included loss of objectivity, inducing risk and difficulty demonstrating effectiveness. Interpretation: Our findings indicate that half of obesity specialists HCPs in our sample of 82 providers, who are primarily dieticians and psychologists, have an implicit weight bias against PLwO. HCPs feel that a weight-focused approach within services was a barrier to patient care, but that there is a lack of alternative non-weight focused measures. Further research is needed into substitute outcome measures for clinical practice, also seeking the views of PLwO, and into interventions to address implicit weight bias. Funding: Johnson & Johnson funded the BiasProof licence and publication open access charge.